Akuisisi Bukti Digital Pada Instagram Messenger Berbasis Android Menggunakan Metode National Institute Of Justice (NIJ) - Imam Riadi; Anton Yudhana; Muhamad Caesar Febriansyah Putra (Jurnal Teknik Informatika dan Sistem Informasi, 2018)
The development of social media especially Instagram application is very rapidly. Instagram users usually do activities at any time by using Instagram as a communication tool for sharing information using Android smartphones. A large number of Instagram users makes this application vulnerable to Instagram abuse such as cyberbullying crime among Instagram users. The cases can be examined to obtain digital evidence in the form of chats and images/photos in Android smartphone. Investigations in this study use the National Institute of Justice (NIJ) method that provides several stages of preparation, collection, examination, analysis, and reporting while forensic applications use OXYGEN forensics. The process of data acquisition using OXYGEN forensics obtains evidence of data results in the form of photos/pictures and conversations on the Instagram messenger.